2013
DOI: 10.1111/jspn.12057
|View full text |Cite
|
Sign up to set email alerts
|

A review of clinical manifestations in adolescent and young adults after use of synthetic cannabinoids

Abstract: Nurses provide the most direct and supportive care to patients who present for medical treatment after the use of SCs. Knowledge of clinical manifestations can facilitate supportive management of patients suspected of SCs use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 32 publications
1
51
0
Order By: Relevance
“…Since SCs' producers often change formulas to avoid detection, users' experience may vary over time [25]. The most common adverse effects include: tachycardia, agitation, nausea, anxiety, irritability, drowsiness, hallucinations, delusions, hypertension, confusion, dizziness, vertigo and chest pain, besides cardiovascular, cerebrovascular, neurological and renal problems [24], some of which may have a lethal outcome [26,27].…”
Section: Adverse Effectsmentioning
confidence: 99%
“…Since SCs' producers often change formulas to avoid detection, users' experience may vary over time [25]. The most common adverse effects include: tachycardia, agitation, nausea, anxiety, irritability, drowsiness, hallucinations, delusions, hypertension, confusion, dizziness, vertigo and chest pain, besides cardiovascular, cerebrovascular, neurological and renal problems [24], some of which may have a lethal outcome [26,27].…”
Section: Adverse Effectsmentioning
confidence: 99%
“…Psychotic disturbances of the paranoid type, and signs such as anxiety, agitation, irritability, convulsions, fainting, nausea and vomiting and hypokalaemia can also be observed. Finally, alongside neuropsychiatric effects, [84][85][86][87] cardiovascular effects have more recently been described, [84,88,89] including tachycardia, palpitations, hypertension, chest pain, myocardial infarct, and one case of heart arrest in a patient with coronary disease.…”
Section: Synthetic Cannabinoidsmentioning
confidence: 99%
“…This diversity, much more so than for other synthetic substances, explains the unforeseeable nature of the damaging effects of the use of "Spice" or synthetic cannabinoids. [85] …”
Section: Synthetic Cannabinoidsmentioning
confidence: 99%
“…Use of SC is reported to be popular especially among teens and young adults (1). SCs began to be marketed through supermarkets and internet since 2004 in Europe.…”
Section: Introductionmentioning
confidence: 99%
“…While it was found that users in Europe and the US are mostly adolescent and young adult males (1,6), SC using age in Japan was reported to be higher when compared to Western countries (5). It was found in studies that the use of other psychoactive substances with SC is common and the most commonly used psycho-active agents are alcohol and cannabis (7).…”
Section: Introductionmentioning
confidence: 99%